The Infamous Harry Hayward : A True Account of Murder and Mesmerism in Gilded Age Minneapolis - Peters, Shawn Francis, 1966- (Book collections on Project MUSE., 2018)
On a winter night in 1894, a young woman's body was found in the middle of a road near Lake Calhoun on the outskirts of Minneapolis. She had been shot through the head. The murder of Kittie Ging, a twenty-nine-year-old dressmaker, was the final act in a melodrama of seduction and betrayal, petty crimes and monstrous deeds that would obsess reporters and their readers across the nation when the man who likely arranged her killing came to trial the following spring. Shawn Francis Peters unravels that sordid, spellbinding story in his account of the trial of Harry Hayward, a serial seducer and schemer whom some deemed a "Svengali," others a "Machiavelli," and others a "lunatic" and "man without a soul." Dubbed "one of the greatest criminals the world has ever seen" by the famed detective William Pinkerton, Harry Hayward was an inveterate and cunning plotter of crimes large and small, dabbling in arson, insurance fraud, counterfeiting, and illegal gambling. His life story, told in full for the first time here, takes us into shadowy corners of the nineteenth century, including mesmerism, psychopathy, spiritualism, yellow journalism, and capital punishment. From the horrible fate of an independent young businesswoman who challenged Victorian mores to the shocking confession of Hayward on the eve of his execution (which, if true, would have made him a serial killer), The Infamous Harry Hayward unfolds a transfixing tale of one of the most notorious criminals in America during the Gilded Age"--Viewed on Amazon.com 4-9-2018.